The study on factors affecting job satisfaction and work commitment among Petronas Refinery Petrochemical Corporation (PRPC) staffs, the intermark / Nur Amalina Diyana Suhaimi - Suhaimi, Nur Amalina Diyana (Bachelor of Science (Hons) Statistics, 2015)
This study determines the levels of Job Satisfaction and Work Commitment among PETRONAS Refinery and Petrochemical Corporation (PRPC) Staffs, The Intermark. The relationships between Remuneration, Management Style and Working Environment on Job Satisfaction and Work Commitment are also investigated. A questionnaire titled ‘Modelling Job Satisfaction and Work Commitment among Lecturers: A Case of UiTM Kelantan’ (2010) was modified and developed for this study. The corresponding data were collected from 148 PRPC staffs which are randomly selected in order to prevent bias to occur. The findings suggested that the Remuneration and Working Environment has a significant influence on Job Satisfaction and Work Commitment. The result also proved that Job Satisfaction only play a mediating role in linking the Remuneration and Working Environment with Dependent Variable. Management Style was found not to be associated with Job Satisfaction and Work Commitment. Mediation also did not occur since the indirect path is not significant. The study also proved that Job Satisfaction has an influenced on Work Commitment among PRPC staffs